Hysteresis Current Control technique based on Space Vector Modulation for Active Power Filter - Wang Yun-liang; Guo Qi-liang (Institute of Advanced Engineering and Science, 2011)
In this paper, the hysteresis current control (HCC) technique based on space vector modulation (SVM) for shunt active power filter (APF) is proposed. The switching control algorithms of the HCC based SVM manage to generate compensated current according to the reference current. Harmonics extraction is based on the instantaneous active and reactive power theorem in time domain by calculating the power compensation. A closed loop control system is carried out and the error current is the difference between the reference current which is obtained from the power compensation and the actual current needs to be injected back into the power grid. By implementing this control strategy, the APF manages to generate better compensated harmonics currents to the power grid. Keywords: active power filter, hysteresis current control, space vector modulation ,matlab/simulink.DOI: http://dx.doi.org/10.11591/ijpeds.v1i1.69